2001
DOI: 10.1111/1468-5884.00154
|View full text |Cite
|
Sign up to set email alerts
|

Functional visual field in a rapid serial visual presentation task

Abstract: Dynamic temporal change in the size of functional visual field was measured using a dual task: a peripheral task in which one square in a background pattern of squares was changed in shape to a dot; and a central task involving the rapid serial visual presentation of a sequence of letters (RSVP task). The temporal lag between the occurrences of the dot and the RSVP target was manipulated. University students were asked to detect the dot and to depress a mouse button as quickly as possible while searching for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 17 publications
1
8
0
Order By: Relevance
“…The RSVP task is commonly used as a way of reducing the attentional resources available for other cognitive functions. Kikuchi, Sekine, and Nakamura (2001) reported that in a dual-task condition involving shape change detection and RSVP simultaneously, RSVP captured attentional resources and, consequently, decreased change detection performance. Joseph, Chun, and Nakayama (1997) also reported that in dual-task conditions in which an RSVP task and an orientation discrimination task were performed simultaneously, the RSVP task captured attentional resources and impaired orientation discrimination performance.…”
Section: Introductionmentioning
confidence: 99%
“…The RSVP task is commonly used as a way of reducing the attentional resources available for other cognitive functions. Kikuchi, Sekine, and Nakamura (2001) reported that in a dual-task condition involving shape change detection and RSVP simultaneously, RSVP captured attentional resources and, consequently, decreased change detection performance. Joseph, Chun, and Nakayama (1997) also reported that in dual-task conditions in which an RSVP task and an orientation discrimination task were performed simultaneously, the RSVP task captured attentional resources and impaired orientation discrimination performance.…”
Section: Introductionmentioning
confidence: 99%
“…The rapid serial visual presentation (RSVP) task was chosen in the present study [16,17,18] because the RSVP task is suitable for conducting an experiment that requires continuous viewing of AR images. In the typical RSVP task, stimuli are presented sequentially and very rapidly.…”
Section: Background and Objectivementioning
confidence: 99%
“…The UFOV is the area around the fixation point from which we can acquire information briefly during a visual task . The size of UFOV can vary under different conditions, such as task difficulty and attentional demand . It is possible that using an in‐vehicle information display while driving causes narrowing of the UFOV by increasing an attentional demand.…”
Section: Useful Attention Field Of View (Ufov) For Windshield‐refractmentioning
confidence: 99%
“…12 The size of UFOV can vary under different conditions, such as task difficulty and attentional demand. 13,14 It is possible that using an in-vehicle information display while driving causes narrowing of the UFOV by increasing an attentional demand. However, we expect that UFOV is not narrowed by using monocular AR image presentation because the attentional demand relates to the shift of attention in depth so attentional demand is mitigated by the monocular observation.…”
Section: Useful Attention Field Of View (Ufov) For Windshield-refractmentioning
confidence: 99%